Financial sustainability and financial performance of the SMEs in service sector in Malaysia - Lohana, Sonia (2021)
Over the past few decades, social scientists, and policymakers in both developed and developing countries have realized that entrepreneurs' financial management and knowledge are crucial for forming and sustaining small and medium enterprises (SMEs). SMEs are essential for the economic growth of Malaysia and therefore are considered as a significant source of job creation and poverty reduction as they significantly contribute to the gross domestic products. However, the major weaknesses that constrain SMEs' success in financial performance are the low financial planning, management, and knowledge. This should be of concern to the policymakers, stakeholders, and the government, as SMEs are essential for Malaysia's economic growth. Thus, this study aimed to determine the financial sustainability and financial performance of SMEs in Malaysia. The unit of analysis in this study was the SMEs top management of the business. A quantitative research design was employed, using a self-administrated questionnaire. Accordingly, five hypotheses were then formulated and tested in the survey using the data collected from the 146 respondents selected through a simple random sampling. The study covered Malaysia, which comprised three states, namely Kuala Lumpur, Selangor, and Johor. SMART-PLS was used as a statistical tool for data analysis. This study focused on the dimensions of financial sustainability. Findings indicated positive and significant relationships between dimensions of financial sustainability, namely financial and strategic planning, income diversification and financial literacy, and SMEs financial performance. However, sound administration and finance (SAF) and own income generation (OIG) were found to have a positive and insignificant relationship with SMEs' financial performance. The findings of this study for assessing and managing the enterprise's finance will allow maintaining the stability of FS by monitoring various types of business transactions performed and, if necessary, improving it by monitoring the valuation of the business transaction of an economic entity.